An Analysis of Students’ and Teachers’ Needs of Microlearning-Based Learning Materials for English in Senior High School - Sugiarto, Anrivere Muhammad Azka; Seli, Fenny Yutika (Lembaga Intelektual Muda (LIM) Maluku, 2023)
The purpose of this research is to determine the students' requirements for microlearning-based English teaching materials for grade 12 senior high schools and to discover what the teacher demands on microlearning-based English teaching materials in senior high schools. This research goal was due to the COVID-19 pandemic that had a tremendous influence on Indonesian education, necessitating adaption and the use of technology. Various variables contributed to learning loss among 12th-grade students. Based on explanation above, the respondent of this research consists of 203 12th-grade students and 84 English teachers in Senior High School located mainly in West Jakarta. A need analysis is required because adequate teaching materials are critical for effective English language acquisition. For first research instrument, writer use questionnaire with Likert Scale to ensure trustworthiness and data reliability and conducting interview for second research instrument. This research uses descriptive qualitative method to analyze the demands of students and teachers for microlearning-based learning materials in senior high school English, emphasizing the potential of microlearning for English language instruction. Providing concentrated information that can improve learning and fulfil the requirements of students, which also critical to improve English learning in Indonesia's 2013 curriculum